Roles of Motor Cortex Neuron Classes in Reach-Related Modulation for Hemiparkinsonian Rats - Li, Min; Wang, Xuenan; Yao, Xiaomeng; Wang, Xiaojun; Chen, Feiyu; Zhang, Xiao; Sun, Shuang; He, Feng; Jia, Qingmei; Guo, Mengnan; Chen, Dadian; Sun, Yue; et al. (Frontiers in Neuroscience, 2021)
Disruption of the function of the primary motor cortex (M1) is thought to play a critical role in the motor dysfunctions of Parkinson’s disease (PD). Detailed information regarding which specific aspects of M1 circuits become abnormal remains unclear. We recorded single units and local field potential (LFP) of the M1 neurons by unilaterally 6-hydroxy dopamine (6-OHDA) treated rats and control rats to assess the impact of dopamine (DA) cell loss during rest and forelimb-reaching task. Our results indicated that M1 neurons can be classified into two groups (putative pyramidal neurons and putative interneurons) and that 6-OHDA could induce modifications in the activities of different M1 subpopulations to a large extent. There was a reduced activation of putative pyramidal neurons in inattentive rest and reaching movement. In addition, the 6-OHDA intoxication correlated with an increase in special frequencies of LFP, especially in the beta-range (broadly defined here as any frequency between 12 and 35 Hz) that become pathologically exaggerated throughout cortico-basal ganglia circuits after dopamine depletion. Furthermore, different spike-LFP coupling relationship measures revealed that the putative pyramidal neurons spiking also particularly prone to being exhibited higher incidences of phase-locked to ongoing cortical oscillations at 12-35Hz during reaching movement. Conversely, putative interneurons were neither hypoactive nor synchronized to ongoing cortical oscillations. These data collectively demonstrate a neurons type-selective alteration of M1 for parkinsonian rats. These alterations will hamper M1 contributions to motor instructional conduction and are likely to constitute one of the main contributors underlying the PD motor impairments.